Do pupils at research-informed schools actually perform better? Findings from a study at English schools - Groß Ophoff, Jana; Brown, Chris; Helm, Christoph (Frontiers in Education, 2023)
Across the globe, many national, state, and district level governments are increasingly seeking to bring about school ‘self improvement’ via the fostering of change, which, at best, is based on or informed by research, evidence, and data. According to the conceptualisation of research-informed education as inquiry cycle, it is reasoned that there is value in combining the approaches of data-based decision-making and evidence-informed education. To put this assumption to test, a data-set based on 1457 staff members from 73 English primary schools (school year 2014/2015) was (re-)analysed in this paper. Not only survey information about trust among colleagues, organisational learning and the research use climate was used (cf. Brown et al., 2016), but also the results from the most recent school inspections and the results from standardised assessment at the end of primary school. Of particular interest was, as to whether the perceived research use climate mediates the association between organisational learning and trust at school on the one hand and the average pupil performance on the other, and whether schools that were rated as ‘outstanding’, ‘good’, or ‘requires improvement’ in their most recent school inspection differ in that regard. Data was analysed based on multi-level structural equation modelling. The originality of this paper lies in challenging common claims that teachers’ engagement with research supports development processes at schools and pupil performance. Our findings indicate that schools with a higher average value of trust among colleagues report more organisational and research informed activities, but also demonstrate better results in the average pupil performance assessment at the end of the school year. This was particularly true for schools rated as ‘good’ in previous school inspections. In contrast, both ‘outstanding’ schools and schools that ‘require improvement’ appeared to engage more with research evidence, even though the former seemed not to profit from it. Accordingly, the conclusion is drawn that a comprehensive model of research-informed education contributes to more conceptual clarity in future research, and based on that, contribute to theoretical development.